Thoughts on the NIL Era: An Introduction to the Special Issue - Marshall Magnusen (Journal of Applied Sports Management, 2021)
The goal of this special issue is to inspire scholarship and spark conversation about NIL through a variety of “think pieces” from leading researchers. Sport scholars were invited to combine their expertise with creativity to craft compelling papers about NIL and how it may be interpreted through a variety of disciplinary lenses.
Keywords: Gambling; Governance; NCAA; Recruiting; Sponsorships; Wellbeing